2020
DOI: 10.18488/journal.aefr.2020.107.808.815
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inflation Rates on Stock Market Returns in Sudan: The Linear Autoregressive Distributed Lag Model

Abstract: This study investigates the effect of the inflation rate in Sudan on stock returns on the Khartoum Stock Exchange. The linear autoregressive distributed lag (ARDL) model was applied to monthly data over the period from September 2003 to December 2019, with the exchange and money supply growth rates, and Murabaha profit margin as control variables. As no previous studies have studied the effect of inflation on stock returns by means of the ARDL approach, this study intends to fill this gap in the current body o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
3
7
0
Order By: Relevance
“…Because no one is interested in stock instruments offered by business actors engaged in the production of consumer goods in the capital market, changes in stock prices will inevitably decrease and result in reduced capital gains. The findings of this study are consistent with previous research conducted by Akwe and Garba (2019), Hidayat et al (2018), Basarda et al (2018), Omer Elmahgop and Sayed (2020), and Esti Kontaki and Affid Diena (202 1), indicating that an increase in inflation will have a negative impact on the ability of investors to realize capital gains.…”
Section: Research Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Because no one is interested in stock instruments offered by business actors engaged in the production of consumer goods in the capital market, changes in stock prices will inevitably decrease and result in reduced capital gains. The findings of this study are consistent with previous research conducted by Akwe and Garba (2019), Hidayat et al (2018), Basarda et al (2018), Omer Elmahgop and Sayed (2020), and Esti Kontaki and Affid Diena (202 1), indicating that an increase in inflation will have a negative impact on the ability of investors to realize capital gains.…”
Section: Research Resultssupporting
confidence: 92%
“…Rising evidence that points to the impact of inflation on return on investment include research by Hidayat et al(2018), which shows that inflation negatively impacts return on investment. The results of this study were corroborated by research done by Omer Elmahgop and Ahmed Sayed (2020). They found that inflation levels significantly negatively impacted returns on investments in both short-and long-term time frames.…”
Section: Ma Nufacturing Sector Companiessupporting
confidence: 87%
“…Sudan's economy, particularly in recent years, has suffered from high inflation, fluctuations in exchange rates, supply shortages, and other economic problems. These problems, especially high inflation and fluctuations in exchange rates, negatively affect the Khartoum Stock market returns as much as stock prices (Omer and Ahmed 2020;Mohamed and Elmahgop 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Fisher's [8] work assumed that the monetary and real sectors of the economy were largely independent. As a result, the expected returns on assets, such as stocks, should move one-to-one with inflation rates, providing a hedge against inflation [12]. This concept is referred to as the Fisher effect, also known as the Fisher hypothesis.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…As reported by the Central bank of Nigeria (CBN) in its annual statistical bulletin, the inflation rate was as high as 18.6% in 2016 and has consistently remained high since then, closing at 15.75% in December 2020. Therefore, understanding the impact of inflation on stock returns is critical, not only for investors but also for researchers, policymakers, and financial analysts [12].…”
Section: Introductionmentioning
confidence: 99%